Neurosyphilis after treatment of latent syphilis with benzathine penicillin. - Jørgensen, J (1986)
Two patients developed neurosyphilis after treatment of latent syphilis with intramuscular benzathine penicillin. The cases confirm recent investigations that show that neither benzathine penicillin nor procaine penicillin in the standard doses results in treponemicidal concentrations of penicillin in cerebrospinal fluid. Neurosyphilis can be treated effectively by intravenous benzylpenicillin infusions of 18 to 21.6 g daily for 15 days.